2020
DOI: 10.3390/cancers12102910
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Pathway as a Source of Vulnerability in IDH1mut Glioma

Abstract: In addition to providing integrity to cellular structure, the various classes of lipids participate in a multitude of functions including secondary messengers, receptor stimulation, lymphocyte trafficking, inflammation, angiogenesis, cell migration, proliferation, necrosis and apoptosis, thus highlighting the importance of understanding their role in the tumor phenotype. In the context of IDH1mut glioma, investigations focused on metabolic alterations involving lipidomics’ present potential to uncover novel vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(73 citation statements)
references
References 30 publications
5
66
2
Order By: Relevance
“…Interestingly, the results revealed that gliomas, which are higher malignancy neoplasms compared to meningiomas, contained higher amounts of ceramides and their derivates (i.e., HexCer), while meningiomas contained higher levels of SMs, PCs, PEs, and LPCs (Figure S3 and Table S3). These alterations did not align with previous reports on biochemical alterations in gliomas compared to healthy tissue [6,41,42]; thus, further studies, possibly including spatially resolved in vivo sampling of healthy and cancerous tissue, are required to investigate this discrepancy in greater depth. It must also emphasized that the above-described comparison was performed as a proof-of-concept to verify the proposed method's applicability for the differentiation of brain tumors, and that further in-depth biological interpretation and discussion of these results was not undertaken, as currently available clinical tools already enable the easy identification of these lesions [25].…”
Section: Discussioncontrasting
confidence: 76%
“…Interestingly, the results revealed that gliomas, which are higher malignancy neoplasms compared to meningiomas, contained higher amounts of ceramides and their derivates (i.e., HexCer), while meningiomas contained higher levels of SMs, PCs, PEs, and LPCs (Figure S3 and Table S3). These alterations did not align with previous reports on biochemical alterations in gliomas compared to healthy tissue [6,41,42]; thus, further studies, possibly including spatially resolved in vivo sampling of healthy and cancerous tissue, are required to investigate this discrepancy in greater depth. It must also emphasized that the above-described comparison was performed as a proof-of-concept to verify the proposed method's applicability for the differentiation of brain tumors, and that further in-depth biological interpretation and discussion of these results was not undertaken, as currently available clinical tools already enable the easy identification of these lesions [25].…”
Section: Discussioncontrasting
confidence: 76%
“…Besides, it was found that sphingomyelin and monounsaturated fatty acids are accumulated in these organelles in IDH1-mutant cells. Based on this finding, the same group recently demonstrated that boosting these pathways via the addition of N,N-dimethylsphingosine (NDMS) and sphingosine C17 induced an apoptotic response in IDH1-mutant glioma cells [61].…”
Section: Lipid Metabolismmentioning
confidence: 98%
“…Ceramide is also an important factor in apoptosis with its mechanism having been studied in depth [15]. In addition, because of an in vitro experiment assessing glioma treatment confirmed that apoptosis occurred when sphingosine kinase was inhibited in IDH cells and when sphingosine-1-phosphate production was inhibited [16]. However, no studies have yet been performed examining the association between phytosphingosines and CRC; meanwhile, they have been shown to induce inhibition of epithelial mesenchymal transition-related protein expression in malignant breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%